Schita de sistematizare a alternantelor morfonologice (pe baza materialului flexionar) - Cychnerski, Tomasz (Wydawnictwo Naukowe UAM, 2007)
This paper continues and implements several other ones concerning the morphonology of the standard contemporary Romanian. It analyzes all the alternations which appear in the structure of the inflectional root according to seven criteria: (1) phonological status of the alternating terms, (2) phonological process realized by the alternation, (3) factors conditioning the alternation, (4) grammatical domain in which the alternation occurs, (5) regularity of the alternation, (6) its productiveness and (7) its functions.
Systematisation of the morphonological alternations. An outline based on the inflectional material
Keywords: morphonology; contemporary Romanian; alternations; inflectional material